Microtubule poleward flux in human cells is driven by the coordinated action of four kinesins. (19th October 2020) - Steblyanko, Yulia; Rajendraprasad, Girish; Osswald, Mariana; Eibes, Susana; Jacome, Ariana; Geley, Stephan; Pereira, António J; Maiato, Helder; Barisic, Marin
Abstract: Mitotic spindle microtubules (MTs) undergo continuous poleward flux, whose driving force and function in humans remain unclear. Here, we combined loss‐of‐function screenings with analysis of MT‐dynamics in human cells to investigate the molecular mechanisms underlying MT‐flux. We report that kinesin‐7/CENP‐E at kinetochores (KTs) is the predominant driver of MT‐flux in early prometaphase, while kinesin‐4/KIF4A on chromosome arms facilitates MT‐flux during late prometaphase and metaphase. Both these activities work in coordination with kinesin‐5/EG5 and kinesin‐12/KIF15, and our data suggest that the MT‐flux driving force is transmitted from non‐KT‐MTs to KT‐MTs by the MT couplers HSET and NuMA. Additionally, we found that the MT‐flux rate correlates with spindle length, and this correlation depends on the establishment of stable end‐on KT‐MT attachments. Strikingly, we find that MT‐flux is required to regulate spindle length by counteracting kinesin 13/MCAK‐dependent MT‐depolymerization. Thus, our study unveils the long‐sought mechanism of MT‐flux in human cells as relying on the coordinated action of four kinesins to compensate for MT‐depolymerization and regulate spindle length. Synopsis: The phenomenon of continuous poleward flux of mitotic spindle microtubules has remained mysterious. This study establishes the long‐sought molecular mechanisms underlying microtubule flux, and explains its role in regulating spindle length upon establishment of stable end‐on kinetochore‐microtubule attachments Mitotic microtubule flux in human cells is sequentially driven by the coordinated action of four kinesins. Microtubule‐sliding motors EG5 and KIF15 collaboratively act on interpolar microtubules, assisted by CENPE at kinetochores in prometaphase and KIF4A on chromosome arms in metaphase. Microtubule‐crosslinking proteins HSET and NuMA facilitate distribution of microtubule flux‐associated spindle forces on metaphase chromosomes, enabling kinetochore microtubule flux due to coupling with non‐kinetochore microtubules. Microtubule poleward flux regulates spindle length in response to MCAK‐mediated depolymerization of kinetochore microtubules. Abstract : The mysterious phenomenon of continuous mitotic microtubule flux is found to be associated with regulation of spindle length after establishment of stable end‐on kinetochore‐microtubule attachments.